FEM-based analysis of the relationship between track insulation conductivity and stray current in DC traction systems - Aussawamaykin, Apiwat; Pao-la-or, Padej (Institute of Advanced Engineering and Science, 2025)
This research investigates the influence of track insulation conductivity on stray current in direct current (DC) traction systems, which is a significant issue in railway operations due to its potential to cause electrochemical corrosion. Utilizing the finite element method (FEM), a simplified geometric model of a DC tram traction system was analyzed under varying conditions of track insulation conductivity. The study examined three levels of insulation conductivity, represented by fastener resistances of 1,000 Ω, 3,000 Ω, and 6,000 Ω, to understand their impact on stray current density. Results revealed that increased insulation resistance leads to reduced stray current density, demonstrating the critical role of track insulation in mitigating stray currents. The study further highlights that the depth of soil beneath the track also significantly affects stray current distribution. These findings provide insights into improving track design and maintenance for better protection against the negative effects of stray current in DC traction systems.